Childhood trauma, attachment orientation, and complex PTSD (CPTSD) symptoms in a clinical sample: Implications for treatment. (15th August 2022) - Karatzias, Thanos; Shevlin, Mark; Ford, Julian D.; Fyvie, Claire; Grandison, Graeme; Hyland, Philip; Cloitre, Marylene
Abstract: Although there has been significant work on the association between posttraumatic stress disorder (PTSD) and attachment orientation, this is less the case for complex PTSD (CPTSD). The primary aim of this paper was to assess the strength of the association between the four adult attachment styles (i.e., secure, dismissing, preoccupied, and fearful) and severity of CPTSD symptoms (i.e., symptoms of PTSD and disturbances in self-organization [DSO]). We hypothesized that attachment orientation would be more strongly associated with DSO symptoms compared to PTSD symptoms. A trauma exposed clinical sample ( N = 331) completed self-report measures of traumatic life events, CPTSD symptoms, and attachment orientation. It was found that secure attachment and fearful attachment were significantly associated with DSO symptoms but not with PTSD symptoms. Dismissing attachment style was significantly associated with PTSD and DSO symptoms. Preoccupied attachment was not significantly associated with CPTSD symptoms. Treatment implications for CPTSD using an attachment framework are discussed.